The investigation of the production method influence on the structure and properties of the ferroelectric nonwoven materials based on vinylidene fluoride – tetrafluoroethylene copolymer; Materials Chemistry and Physics; Vol. 182 - Bolbasov E. N. Evgeny Nikolaevich; Stankevich K. S. Ksenia Sergeevna; Sudarev E. A. Evgeniy Aleksandrovich; Bouznik V. M. Vyacheslav Mikhaylovich; Kudryavtseva V. L. Valeriya Lvovna; Antonova L. V. Larisa Valerjevna; Matveeva V. G. Vera Gennadjevna; Anissimov Yu. G. Yuri; Tverdokhlebov S. I. Sergei Ivanovich (2016, 2016)
Title screen